Simulation and Analysis of Contactless Solar Evaporation - YU Jie, XU Zhenyuan (Shanghai Jiaotong Daxue xuebao, 2023)
Zero-liquid discharge is an efficient pathway for high concentration brine and wastewater treatment. Contactless solar evaporation is a new configuration proposed in recent years towards this target, which has the advantages of solar energy utilization, simple structure, passive operation, and anti-fouling. Considering that contactless solar evaporation lacks an effective predictive model to guide the optimization in real scenarios, a steady-state thermal resistance network model is developed for the first time and further analyses are conducted. According to the results, two main heat sources of the water, radiative heat transfer and air gap heat transfer, contribute 54.2% and 45.8% to the total heat flow and both have a significant impact on the evaporation performance. The larger air gap thickness has a negative effect on both of the two heat transfer processes. The evaporation rate with an air gap thickness of 10 mm is only 70% of that with an air gap thickness of 4 mm. Additionally, decreasing vapor diffusion resistance is an efficient way to increase the evaporation rate. The evaporation rate triples when the vapor diffusion coefficient increases from 5×10-6 m2/s to 2.5×10-5 m2/s.